2017
DOI: 10.1002/2016wr019707
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated hydraulic properties of Sphagnum moss and peat reveal trimodal pore‐size distributions

Abstract: In ombrotrophic peatlands, the moisture content of the vadose zone (acrotelm) controls oxygen diffusion rates, redox state, and the turnover of organic matter. Whether peatlands act as sinks or sources of atmospheric carbon thus relies on variably saturated flow processes. The Richards equation is the standard model for water flow in soils, but it is not clear whether it can be applied to simulate water flow in live Sphagnum moss. Transient laboratory evaporation experiments were conducted to observe evaporati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
75
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 117 publications
8
75
0
Order By: Relevance
“…Under field conditions, soil hydraulic properties (SHP) control the water regime in the topmost, growing part of the peat profile and are thus a critical factor for moss growth and survival (Hájek and Beckett, 2008). The importance of capillary, film, and vapour flow processes for upward water fluxes in moss and peat has been emphasized by Hayward and Clymo (1982) and Price et al (2009), while SHP accounting for these processes have only recently been identified by Weber et al (2017a) for a limited number of samples.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Under field conditions, soil hydraulic properties (SHP) control the water regime in the topmost, growing part of the peat profile and are thus a critical factor for moss growth and survival (Hájek and Beckett, 2008). The importance of capillary, film, and vapour flow processes for upward water fluxes in moss and peat has been emphasized by Hayward and Clymo (1982) and Price et al (2009), while SHP accounting for these processes have only recently been identified by Weber et al (2017a) for a limited number of samples.…”
Section: Introductionmentioning
confidence: 99%
“…Quinton et al, 2008;Price et al, 2008;Price, 2012, 2014;Morris et al, 2015;Weber et al, 2017a). As Sphagnum decomposes, the fibrous material is biochemically broken up into smaller solid fragments (Rezanezhad et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations